Phylogenetic Placement of Foot and Mouth Disease Virus during 2014 in Buffaloes, Egypt - Fahmy, Hanan A.; Khalif, Nashwa O.; Radwan, Mervat E.I. (International Journal For Research In Health Sciences And Nursing, 2016)
Foot-and-mouth disease virus (FMDV) SAT2 serotype is endemic in Egypt since 2012. The objectives of the present study were to investigate strain identification of FMDV infecting water buffaloes (Bubalus bubalis) in April, 2014, Qalyubia, Egypt. Therefore partial sequences were generated after detection by real time RT-PCR and subsequent gel purification of RT-PCR amplified products of VP1 gene of FMDV- SAT2. Partial sequencing of purified virus revealed that SAT2 serotype of FMD was circulating in this region. Sequences were further examined by sequence analysis and subsequent phylogeny to compare these sequences from known strains of FMDV-SAT2 circulating globally and retrieved from GenBank. Nucleotide substitution generates polymorphism at position 13 nucleotide, where a Cytosine replaced a Thymine and at the levels of 22 nucleotide where Guanine substituted Adenosine. A partial sequence of SAT2 showed the highest level of homology 99.4% similarity with sequences from Egypt 2012 with diversion 0.6 but it is variable from its neighbor countries isolates. Phylogenetic analysis showed a robust tree clustering all samples with sequences belonging to the FMDV-SAT2 variant with strong bootstrap values at relevant nodes and the evolutionary distance between groups is very short. There is a substitution in the sequences of amino acids at the position of 8, where an Alanine is changed to a Threonine. These findings demonstrate the recent picture of FMDV-SAT2 which incriminated for buffalo infectivity and responsible for its persistence in the endemic areas. Such epidemiological data could guide the application of efficient control strategies of FMDV in Egypt.